Intelligent robotic system for home services speech recognition and synthesizing - Wang, Cun Zhe (2010)
In the last few decades, robot technologies have been rapidly developed for various uses, such as industry automation, surgical robots, military and exploration. The entertainment and service robotic have also become well known since some manufactures were able to show humanoid robots dancing.